Reconstructing the Imago Dei in the Posthuman Era: An Eschatological Theology of Mediated Embodiment - Zebua, Syukurman; Haninuna, Benyamin; Buntula'bi', Semuel; Pinoa, Stevan Andy; Haluk, Paskalis (Jurnal Theologia, 2025)
This article examines the theological challenges posed by posthumanism to the anthropology of Christian theology, with a focus on the doctrine of imago Dei, the meaning of the body, and the eschatological horizons of the Christian faith. The unit of analysis in this study is a theological discourse on posthumanism—especially transhumanism and critical posthumanism—which is dialogued with systematic theology and reflection of Christian education. The purpose of this research is to reconstruct the understanding of the Imago Dei in the context of the posthuman era and to formulate a theological framework that can critically respond to technological narratives without compromising human dignity or Christian eschatological expectations. This research employs a qualitative method based on literature studies, utilizing a philosophical-theological hermeneutic approach, which enables a critical interpretation of classical and contemporary theological sources, as well as major works in the philosophy of posthumanism and the philosophy of technology. The study's findings reveal that posthumanism exposes the limitations of the substantive-rational imago Dei model and encourages the reconstruction of imago Dei as a relational-eschatological category rooted in communion with God, others, and creation. From this reconstruction was born the eschatological theological concept of the mediated body, which affirms that human existence is always mediated by technology, yet still directed toward its fullness in Christ, not to technological salvation. The primary contribution of this article lies in the formulation of an integrative theological framework for the dialogue between the Christian faith and posthumanism within the context of contemplative theology.